2008
DOI: 10.1182/blood-2007-09-112987
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept plus methylprednisolone as initial therapy for acute graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) is a principal cause of morbidity following allogeneic hematopoietic cell transplantation (HCT). Standard therapy for GVHD, high-dose steroids, results in complete responses (CRs) in 35% of patients. Because tumor necrosis factor-␣ (TNF␣) is an important effector of experimental GVHD, we treated patients with newonset GVHD with steroids plus the TNF␣ inhibitor etanercept on a previously reported pilot trial (n ‫؍‬ 20) and a phase 2 trial (n ‫؍‬ 41). We compared their outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 27 publications
(26 reference statements)
5
115
0
1
Order By: Relevance
“…Dac was chosen because at the time of the study there were no other Table 2 Clinical response according to the grade of aGVHD in each organ at day +30 from treatment Grade I 1 1 0 0 1 1 0 0 3 1 2 0 Grade II 1 1 0 0 1 1 0 0 2 0 1 1 Grade III 6 6 0 0 2 2 0 0 3 0 2 1 Grade IV 4 4 0 0 6 1 3 2 1 0 0 1 Total 12 MoAbs with the same characteristics of manageability and safety. 18 As was observed in earlier reported series of patients undergoing second-line treatment for aGVHD, most of our patients also developed opportunistic infections after therapy with Dac, although no major life-threatening infectious episodes occurred. The heterogeneity of earlier administered immunosuppressive treatments and the limited number of patients make it difficult to define the role of Dac in the development of viral infections.…”
Section: Discussionsupporting
confidence: 85%
“…Dac was chosen because at the time of the study there were no other Table 2 Clinical response according to the grade of aGVHD in each organ at day +30 from treatment Grade I 1 1 0 0 1 1 0 0 3 1 2 0 Grade II 1 1 0 0 1 1 0 0 2 0 1 1 Grade III 6 6 0 0 2 2 0 0 3 0 2 1 Grade IV 4 4 0 0 6 1 3 2 1 0 0 1 Total 12 MoAbs with the same characteristics of manageability and safety. 18 As was observed in earlier reported series of patients undergoing second-line treatment for aGVHD, most of our patients also developed opportunistic infections after therapy with Dac, although no major life-threatening infectious episodes occurred. The heterogeneity of earlier administered immunosuppressive treatments and the limited number of patients make it difficult to define the role of Dac in the development of viral infections.…”
Section: Discussionsupporting
confidence: 85%
“…In a retrospective study, infliximab has been shown to be associated with significant response although the proportion of patients with grade III-IV aGVHD was low and treatment was complicated by infections particularly aspergillus which could be explained by elimination of monocytes-macrophages by infliximab [97,98]. Etanercept also increased infections in clinical trials but not as much as infliximab [81,86]. In a phase III randomized trial of high-dose corticosteroids with or without infliximab including 63 newly diagnosed GVHD patients, no statistically significant difference was found in GVHD-related mortality, non-relapse mortality or overall survival [87].…”
Section: Anti-tnfα Agentsmentioning
confidence: 99%
“…Based on these encouraging results, a randomized phase III trial of steroid and CI with MMF vs steroid and CI has started (BMT CTN Study 0802), but the study was terminated as preliminary results did not show any difference with addition of MMF [82]. Other agents such as basiliximab, daclizumab, antithymocyte globulin (ATG), etanercept and infliximab have also been tested without convincing results [83][84][85][86][87]. Based on these findings, the addition of agents to high-dose steroids in first-line treatment is only recommended in the setting of clinical trials.…”
Section: First-line Treatment Of Acute Gvhdmentioning
confidence: 99%
“…[6][7][8] Such recognition proceeds through a complex cross-talk between host and donor cells, resulting in Graft-versus-host disease S Mastaglio et al the release of soluble effector molecules and activation of cellular players ultimately leading to tissue damage. [9][10][11] Traditionally, the distinction between acute and chronic GvHD was based on the time of onset after transplantation (acute GvHD within 100 days, chronic GvHD 100 days after transplant). More recently, insights into the mechanisms underlying GvHD led to an updated classification based on the specificity of signs and symptoms.…”
Section: Prospectsmentioning
confidence: 99%
“…In the HLA-identical setting, a recent phase II clinical study showed that the combination of etanercept (an antitumor necrosis factor-a,) and systemic corticosteroids is more effective than standard treatment in controlling GvHD (complete response rates: 69 versus 33%; Po0.001), despite similar rates of infectious complications and long-term outcome. 9 In the context of haplo-HSCT, several approaches based on graft manipulation and cell and gene therapy have been developed.…”
Section: Prospectsmentioning
confidence: 99%